2017
DOI: 10.18844/wjet.v9i1.993
|View full text |Cite
|
Sign up to set email alerts
|

Digital technology use by the students and english teachers and self-directed language learning

Abstract: The digital era is a new challenge for teachers. While children get acquainted with the digital technology before the age of six, teachers, who have encountered with the digital world at a later time in their lives, struggle with it. Self-directed learning, which is crucial for lifelong learning, can be enhanced by the use technology particularly beyond the classroom settings. The aim of this study was to examine the difference between the perceptions of 5-8 graders in low and high income groups about their te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 0 publications
1
44
0
3
Order By: Relevance
“…On the contrary, self-directed learning as such, should be led and supported by teachers and the teacher’s role is to lead students towards developing independent critical thinking and learning skills. Such a teacher-supported concept of self-directed learning is also explained in Sert and Boynuegri’s research ( 2017 ) stating that “it is clear that self-directed learning requires classroom context in which learner autonomy is promoted by the teacher” (p. 26). Garrison ( 1997 ) names a self-directed way of learning as “a collaborative constructivist perspective”, explaining that an individual takes responsibility for constructing meaning, while others confirm its worthwhileness, and he states that “the challenge for teachers is to create the educational conditions that will facilitate self-direction” (p. 30).…”
Section: Literature Reviewmentioning
confidence: 82%
“…On the contrary, self-directed learning as such, should be led and supported by teachers and the teacher’s role is to lead students towards developing independent critical thinking and learning skills. Such a teacher-supported concept of self-directed learning is also explained in Sert and Boynuegri’s research ( 2017 ) stating that “it is clear that self-directed learning requires classroom context in which learner autonomy is promoted by the teacher” (p. 26). Garrison ( 1997 ) names a self-directed way of learning as “a collaborative constructivist perspective”, explaining that an individual takes responsibility for constructing meaning, while others confirm its worthwhileness, and he states that “the challenge for teachers is to create the educational conditions that will facilitate self-direction” (p. 30).…”
Section: Literature Reviewmentioning
confidence: 82%
“…The characteristics of multimedia that makes multimedia have its own features, this is indicated that multimedia being able to provide an interactive process and providing ease of feedback, multimedia providing freedom and convenience for students to choose learning topics with systematic control (Munir, 2010: 235). The use of technology in the classroom allows students to have competence regarding a particular technology, then in the learning process that is supported by the use of technology will bring about the independence of student learning because the learning process remains student-centered (Sert & Boynueğri, 2017). Interactive multimedia used in the learning process will be able to attract the attention of students so that students will focus on implementing learning activities.…”
Section: Multimedia (Interactive) Learningmentioning
confidence: 99%
“…According to Knowles (), self‐directed learning is the “process in which individuals take the initiative with or without the help of others, in diagnosing their learning needs, formulating learning goals, identifying human and material resources for learning, choosing and implementing learning strategies, and evaluating learning outcomes” (p. 18). Recently, the concept of self‐directed learning has shifted from inside to outside the classroom because “self‐directed learning usually occurs outside the classroom where the students take responsibility of their own learning” (Sert & Boynuegri, , p. 26). Thus, the role of English teachers is to facilitate learning and to train their students to be better prepared to learn independently and effectively both inside and outside of the classroom (Morrison, ).…”
Section: Review Of Literaturementioning
confidence: 99%